Late-Stage Löffler's Endocarditis Mimicking Cardiac Tumor: A Case Report - Koyama, Takafumi; Yamamoto, Hiroyuki; Matsumoto, Manabu; Isogai, Jun; Isomura, Tadashi; Tanaka, Shinji (Frontiers in Cardiovascular Medicine, 2020)
Löffler’s endocarditis (cardiac involvement in hypereosinophilic syndrome) is rare yet life-threatening if left untreated. We describe a case of hypereosinophilic syndrome presenting as a cardiac mass with an abnormal electrocardiogram. Diagnostic studies of the cardiac mass strongly suggested a malignant cardiac tumor invading the papillary muscle. Thus, excision of the cardiac mass and endomyocardial resection with mitral valve replacement were successfully performed. Pathology revealed various stages of thrombosis and irreversible myocardial damage caused by eosinophilic infiltration with no malignancy, leading to the correct diagnosis of late-stage Löffler’s endocarditis. The subsequent combination of anticoagulation and corticosteroids was effective with a favorable outcome. This case highlights pitfalls in multimodality imaging of cardiac thrombus and the clinical significance of considering Löffler’s endocarditis in the diagnostic work-up of a cardiac mass.